Parental Assortative Mating and the Intergenerational Transmission of Human Capital - Paul Bingley; Lorenzo Cappellari; Konstantinos Tatsiramos (Institute of Labor Economics (IZA), 2021)
We study the contribution of parental similarity in schooling levels to the intergenerational transmission of educational attainment. We develop an empirical model for educational correlations within the family in which parental sorting can translate into intergenerational transmission, or transmission can originate from each parent independently. Estimating the model using educational attainment from Danish population-based administrative data for over 400,000 families, we find that about 75 percent of the intergenerational correlation in education is driven by the joint contribution of the parents. We also document a sizeable secular decline of parental assortative mating in education, with a corresponding fall in joint intergenerational transmission from both parents; a fall compensated by an increase in parent-specific intergenerational transmission, leaving total intergenerational persistence unchanged. The mechanisms of intergenerational transmission have changed, with an increased importance of one-to-one parent-child relationships.
Keywords: I24; J62; 330; assortative mating; intergenerational transmission; human capital; inequality